2017
DOI: 10.1007/s10561-017-9640-7
|View full text |Cite|
|
Sign up to set email alerts
|

Comparison of the effect of activated or non-activated PRP in various concentrations on osteoblast and fibroblast cell line proliferation

Abstract: Platelet-rich plasma (PRP) contains growth factors which positively affect cell proliferation, cell differentiation, chemotaxis and intracellular matrix synthesis. All these processes are involved in wound healing and tissue regeneration; thus, PRP as a source of growth factors can be used in periodontal regenerative therapies. The purpose of the present study was to assess the effect of various concentrations of activated and non-activated PRP on proliferation of osteoblasts and fibroblasts in vitro. PRP was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 34 publications
0
21
1
Order By: Relevance
“…Longer PRP evaluation periods may be required as fibroblast cell inhibition occurred between 0 to 24h, and on day seven fibroblast proliferation achieved statistical significance [16]. Another study realised no significance occurred in fibroblast proliferation from 24 to 72-h after the co-culture of PRP, and at this time the higher concentrations exhibited cell inhibition [50]. To the contrary, another study displayed that high concentrations (0.3-5 x 10 6 plt/l) did not cause cell inhibition for up to 72-h and achieved the greatest proliferation up to 2 x 10 6 plt/l.…”
Section: Impact Of Prp On Fibroblastsmentioning
confidence: 99%
“…Longer PRP evaluation periods may be required as fibroblast cell inhibition occurred between 0 to 24h, and on day seven fibroblast proliferation achieved statistical significance [16]. Another study realised no significance occurred in fibroblast proliferation from 24 to 72-h after the co-culture of PRP, and at this time the higher concentrations exhibited cell inhibition [50]. To the contrary, another study displayed that high concentrations (0.3-5 x 10 6 plt/l) did not cause cell inhibition for up to 72-h and achieved the greatest proliferation up to 2 x 10 6 plt/l.…”
Section: Impact Of Prp On Fibroblastsmentioning
confidence: 99%
“…For this purpose, many physicians prefer to activate PRP using various activation methods, such as use of calcium chloride, collagen, thrombin, calcium chloride/thrombin mixture, or freeze/thaw cycle . However, these methods are associated with concerns of early washout of the released growth factors, prompting other physicians to use non‐activated PRP, thereby relying on native collagen at the desired site to promote activation, resulting in slow growth factor release . To clarify the effect of activation on growth factor release, we evaluated the growth factor concentration with and without activation in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…25,27 However, these methods are associated with concerns of early washout of the released growth factors, JOURNAL OF ORTHOPAEDIC RESEARCH ® APRIL 2020 prompting other physicians to use non-activated PRP, thereby relying on native collagen at the desired site to promote activation, resulting in slow growth factor release. 20,[22][23][24] To clarify the effect of activation on growth factor release, we evaluated the growth factor concentration with and without activation in the present study. In accordance with the findings of Oh et al, 26 our study showed that some degree of growth factor existed before the intentional exogenous activation of PRP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vahabi et al made this comparison using calcium gluconate as an activator, by means of cell proliferation determination (of osteoblasts and fibroblasts in vitro ). They observed that in the function of time, activated PRP had a higher effect on cell proliferation than nonactivated PRP, although these results were not statistically significant (Vahabi, Yadegari, & Mohammad‐Rahimi, ).…”
Section: Obtaining Prpmentioning
confidence: 99%